PENGARUH ENDORSE, INFLUENCER, MARKETING DAN IKLAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA RUMAH MAKAN PONDOK HIJAU GUNUNG TUA - Nasution, Anggina Oktaviana; Syahputra, Risky; Nasution, Meisa Fitri (Universitas Wiralodra, 2025)
In the ever-evolving digital era, the use of endorsements, influencers, marketing and social media has become an increasingly popular marketing strategy and is believed to be able to influence consumer behavior. This study aims to determine the effect of endorsements, influencers, marketing, and social media advertising on consumer purchasing decisions towards Pondok Hijau restaurants. The method used in this study is quantitative and data is obtained through the distribution of questionnaires with a sample of 98 respondents who are customers of Pondok Hijau restaurants. The analysis method applied in this study is the multiple linear regression technique using SmartPLS as a tool. The research findings indicate that endorsements, influencers, marketing, and advertising on social media platforms have a positive and significant impact on consumer purchasing decisions, both individually and simultaneously. From this study, the most dominant is endorsement at 0.276 or 27.6%. The results of the R2 test as evidence that it is able to explain the dependent variable that has been studied, namely the consumer purchasing decision variable of 0.722 or 72.2%. This finding provides important implications for business actors in designing effective promotional strategies in the digital era.